Actual Risk of Using Very Aged Donors for Unselected Liver Transplant Candidates: A European Single-center Experience in the MELD Era. Issue 2 (February 2017) - Bertuzzo, Valentina Rosa; Cescon, Matteo; Odaldi, Federica; Di Laudo, Marco; Cucchetti, Alessandro; Ravaioli, Matteo; Del Gaudio, Massimo; Ercolani, Giorgio; D'Errico, Antonietta; Pinna, Antonio Daniele
Abstract : Objective: To evaluate the whole experience of liver transplantation (LT) with donors ≥70 years in a single center not applying specific donor/recipient matching criteria. Background: LT with very old donors has historically been associated with poorer outcomes. With the increasing average donor age and the advent of Model for End-stage Liver Diseases (MELD) score-based allocation criteria, an optimal donor/recipient matching is often unsuitable. Methods: Outcomes of all types of LTs were compared according to 4 study groups: patients transplanted between 1998 and 2003 with donors <70 (group 1, n = 396) or ≥70 years (group 2, n = 88); patients transplanted between 2004 and 2010 with donors <70 (group 3, n = 409), or ≥70 years (group 4, n = 190). From 2003, graft histology was routinely available before cross-clamping, and MELD-driven allocation was adopted. Results: Groups 1 and 2 were similar for main donor and recipient variables, and surgical details. Group 4 had shorter donor ICU stay, lower rate of moderate-to-severe graft macrosteatosis (2.3% vs 8%), and higher recipient MELD score (22 vs 19) versus group 3. After 2003, median donor age, recipient age, and MELD score significantly increased, whereas moderate-to-severe macrosteatosis and ischemia time decreased. Five-year graft survival was 63.6% in group 1 versus 59.1% in group 2 ( P = 0.252) and 70.9% in group 3 versus 67.6% in group 4 ( P = 0.129). Transplants performed between 1998 and 2003, recipient HCV infection, balance of risk score >18, and pre-LT renal replacement treatments were independently associated with worse graft survival. Conclusions: Even without specific donor/recipient matching criteria, the outcomes of LT with donors ≥70 and <70 years are comparable with appropriate donor management.